2019
DOI: 10.1111/ocr.12337
|View full text |Cite
|
Sign up to set email alerts
|

Root resorption in orthodontic treatment with clear aligners: A systematic review and meta‐analysis

Abstract: The aim of this study was to investigate the external root resorption in participants receiving clear aligners and compare it with those treated with fixed appliances. Systematic review with meta‐analysis. Electronic and manual search were performed, and specific inclusion and exclusion criteria were used. Data extraction and analysis were conducted by two investigators independently. The original outcome underwent statistical pooling by Review Manager 5. The quality of studies was assessed by ROBINS‐I tool. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 33 publications
2
34
0
4
Order By: Relevance
“…Respecto a los factores de riesgo asociados al tratamiento ortodóncico, una magnitud de fuerza mayor a 150 gr/cm 2 induce significativamente un mayor riesgo de sufrir RRE que las fuerzas ligeras 3,4,7,11,18,22,24,27,28,29 . Las fuerzas continuas y/o controladas, que se activan cada 4 semanas que permiten la recuperación biológica, generan menos reabsorción en comparación con las fuerzas intermitentes y/o descontroladas propiciadas por ejemplo por aparatos removibles 3,4,7,9,11,14,17,18,22,23,28 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Respecto a los factores de riesgo asociados al tratamiento ortodóncico, una magnitud de fuerza mayor a 150 gr/cm 2 induce significativamente un mayor riesgo de sufrir RRE que las fuerzas ligeras 3,4,7,11,18,22,24,27,28,29 . Las fuerzas continuas y/o controladas, que se activan cada 4 semanas que permiten la recuperación biológica, generan menos reabsorción en comparación con las fuerzas intermitentes y/o descontroladas propiciadas por ejemplo por aparatos removibles 3,4,7,9,11,14,17,18,22,23,28 .…”
Section: Discussionunclassified
“…Los alineadores removibles (invisalign) no generan mayor predisposición a este fenómeno en comparación con la aparatología fija, esto puede deberse a que los protocolos actuales del uso de aparatología fija usa fuerzas ligeras en cada paso 11,16,29,32 , Fang y colaboradores exponen que si existe la colaboración del paciente y un tratamiento bien diseñado por parte del ortodoncista (alineadores removibles), se pueden predecir los movimientos, evitando movimientos repetidos y reduciendo la posibilidad de que se produzca esta complicación al ser comparada con la aparatología fija 27 .…”
Section: Discussionunclassified
“…Neben den allgemein bekannten Vorteilen der FolienTherapie im Bereich der Ästhetik, des Dekalzifizierungsrisi kos und der parodontalen Situation [13][14][15] schützen die Aligner während der kieferorthopädischen Therapie zusätzlich vor weiterem Zahnhartsubstanzverlust. Das Risiko für eine externe Wurzelresorption wird dabei in der Literatur im Vergleich zur Multibrackettherapie als geringer eingeschätzt [16,17].…”
Section: G-h)unclassified
“…The clinical efficiency of these appliances associated with comfort in relation to traditional fixed appliances (FA) has been identified as contributing factors for their large-scale use. 9,10 Studies have investigated the clinical efficacy of aligners and their effects on root resorption, 11 periodontal health, 12 perception of pain and discomfort. 10 It has been reported that orthodontic aligners could be an alternative option for orthodontic treatment in patients with temporomandibular disorder (TMD) 13 and sleep bruxism.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Studies have investigated the clinical efficacy of aligners and their effects on root resorption, 11 periodontal health, 12 perception of pain and discomfort 10 . It has been reported that orthodontic aligners could be an alternative option for orthodontic treatment in patients with temporomandibular disorder (TMD) 13 and sleep bruxism 9 .…”
Section: Introductionmentioning
confidence: 99%